Eric Smith - A Renal Physiology Case-based Learning Exercise - Ansley Splinter; Daniel Castellanos; Carla Lupi (Association of American Medical Colleges, 2013)
Abstract Introduction This progressively disclosed case of a boy presenting with generalized edema was created as part of a case-based learning course for second- and third-year medical students and was designed to integrate with basic science and clinical learning. The case provides a strong opportunity for initial learning and/or targeted review of important pathophysiologic concepts. Methods This case is designed for the small-group format; we have used it with groups ranging from four to eight students. When possible, groups have been facilitated by one basic science and one clinical faculty member. Nonetheless, a clinician well versed in the case and familiar with basic renal physiology can run the session alone. Results We have used this case during our second-year organ system courses. Student ratings of this case have been uniformly high, with the common reaction that the case is critical in helping them integrate lecture and laboratory-based learning. They prefer to participate in these exercises toward the end of the organ system module, citing greater integrative value at this point. Discussion We have found that initial participation in this case is preparing students well for robust involvement in the more open-ended and complex problem-based learning cases of our third year. We have yet to conduct any systematic assessment of learning from participation in these cases.